Impact of age and gender on lymphocyte subset counts in patients with COVID‐19. Issue 2 (23rd June 2021) - Löhr, Phillip; Schiele, Stefan; Arndt, Tim Tobias; Grützner, Stefanie; Claus, Rainer; Römmele, Christoph; Müller, Gernot; Schmid, Christoph; Dennehy, Kevin M.; Rank, Andreas
Abstract: In symptomatic patients with acute Coronavirus disease 2019 (COVID‐19), lymphocytopenia is one of the most prominent laboratory findings. However, to date age and gender have not been considered in assessment of COVID‐19‐related cell count alterations. In this study, the impact of COVID‐19 as well as age and gender on a large variety of lymphocyte subsets was analyzed in 33 COVID‐19 patients and compared with cell counts in 50 healthy humans. We confirm that cell counts of total lymphocytes, B, NK, cytotoxic and helper T cells are reduced in patients with severe COVID‐19, and this tendency was observed in patients with moderate COVID‐19. Decreased cell counts were also found in all subsets of these cell types, except for CD4+ and CD8+ effector memory RA+ (EMRA) and terminal effector CD8+ cells. In multivariate analysis however, we show that in addition to COVID‐19, there is an age‐dependent reduction of total, central memory (CM), and early CD8+ cell subsets, as well as naïve, CM, and regulatory CD4+ cell subsets. Remarkably, reduced naïve CD8+ cell counts could be attributed to age alone, and not to COVID‐19. By contrast, decreases in other subsets could be largely attributed to COVID‐19, and only partly to age. In addition to COVID‐19, male gender was a major factor influencing lower counts of CD3+ and CD4+ lymphocyte numbers. Our study confirms that cell counts of lymphocytes and their subsets are reduced in patients with COVID‐19, but that age and gender must be considered when interpreting the altered cell counts.